2016
DOI: 10.1186/s12864-016-3304-z
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput gene-expression quantification of grapevine defense responses in the field using microfluidic dynamic arrays

Abstract: BackgroundThe fight against grapevine diseases due to biotrophic pathogens usually requires the massive use of chemical fungicides with harmful environmental effects. An alternative strategy could be the use of compounds able to stimulate plant immune responses which significantly limit the development of pathogens in laboratory conditions. However, the efficiency of this strategy in natura is still insufficient to be included in pest management programs. To understand and to improve the mode of action of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…PE changed the expression of all studied defense-related genes, which is in common with other documented elicitors ( Aziz et al, 2007 ; Lachhab et al, 2014 ; Dufour et al, 2016 ). Interestingly, using cell suspensions, we showed that PE simultaneously upregulated the expression of 9-LOX and repressed 13-LOX one.…”
Section: Discussionsupporting
confidence: 70%
“…PE changed the expression of all studied defense-related genes, which is in common with other documented elicitors ( Aziz et al, 2007 ; Lachhab et al, 2014 ; Dufour et al, 2016 ). Interestingly, using cell suspensions, we showed that PE simultaneously upregulated the expression of 9-LOX and repressed 13-LOX one.…”
Section: Discussionsupporting
confidence: 70%
“…Several defense reactions of the plant were observed and measured after PP treatment, for example, papilla formation, lignification, ethylene biosynthesis, phenylalanine ammonia lyase activation, or accumulation of phytoalexins [ 17 ], but have never been analyzed in berries in detail. However, grapevines treated with the phosphonate fosetyl-aluminum showed only a very weak induction of defense-related genes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grapevines have very dynamic gene expression responses to pathogens [70,71]. The top 150 DEGs for BOD berries were highly enriched with biotic stress genes.…”
Section: Transcript Abundance Of Biotic Stress Genesmentioning
confidence: 99%